2014
DOI: 10.1021/ed500280b
|View full text |Cite
|
Sign up to set email alerts
|

Problem Solving Videos for General Chemistry Review: Students’ Perceptions and Use Patterns

Abstract: We examined the use of problem solving videos (PSVs) as a substitute for general chemistry exam review sessions. We investigated student perceptions of course aspects regarding usefulness for supporting their learning of chemistry content. We also examined how students used the PSVs to further their learning. Students ranked the PSVs as more useful than other course components such as the textbook and exam review sessions. Weekly lectures, back tests, and online homework assignments were also ranked highly. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 21 publications
3
37
0
4
Order By: Relevance
“…This finding is aligned with previous research in which general chemistry students ranked instructor run lectures and online homework as two of the more useful course aspects along with problem solving videos, an optional study resource that was closely aligned to their exams. 34 …”
Section: Resultsmentioning
confidence: 99%
“…This finding is aligned with previous research in which general chemistry students ranked instructor run lectures and online homework as two of the more useful course aspects along with problem solving videos, an optional study resource that was closely aligned to their exams. 34 …”
Section: Resultsmentioning
confidence: 99%
“…Students are able to learn at a self-regulated pace and may revisit the material on demand when needed, as illustrated in the use of problem solving videos for general chemistry. 1 Similarly, the use of computerized assistance for lab instruction (of reaction kinetics) generally has been shown to decrease the time spent by a student learning a skill while at the same time increasing the students' skill. 2 In the literature, most of the reports of use of videos for chemistry wet-lab focus on the faculty development of pre-lab content [3][4][5] and although it is useful for students to prepare for lab classes, it is not integral with or part of the laboratory class where students are actually doing their experiments and learning.…”
Section: Introductionmentioning
confidence: 99%
“…The most popular method to help engineering students online has been the provision of problemsolving videos, often posted on the Learning Management System (LMS) (e.g., Canvas, Blackboard), because it allows students to watch at their own pace and typically allows for visualization of the problems [1]. Viewership of videos typically peaks around exam times, indicating that students are using the videos to prepare for tests [2]- [4]. Research has shown that the majority of students generally enjoy learning through videos [2], [4]- [7].…”
Section: Introductionmentioning
confidence: 99%
“…Viewership of videos typically peaks around exam times, indicating that students are using the videos to prepare for tests [2]- [4]. Research has shown that the majority of students generally enjoy learning through videos [2], [4]- [7]. Approximately 70-85% of students report that they find videos helpful and useful [2], [4], [5] Though such videos may be well-liked, it is important to bridge the gap between how the use of videos relates to the grades received by students.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation